Design of Multi-mode Hydraulic Mechanical Composite Transmission Device for Tractor - Wang Haoran; Cao Fuyi; Ma Ke; Guo Zhanzheng; Guo Fuqiang (Jixie chuandong)
In order to meet the complex and varied working conditions of the tractor， a multi-mode hydraulic mechanical composite transmission device is designed. The device combines the advantages of pure hydraulic， speed-dividing， torque-sharing and other transmission modes. The theoretical analysis of speed regulation characteristic， torque ratio characteristics， power shunt characteristic and efficiency are carried out. The results show that the designed multi-mode hydraulic mechanical composite transmission output torque changes continuously， the transmission efficiency is above 0.8， and in addition to the pure hydraulic mode， the hydraulic power split ratio of other modes is controlled between -0.2~0.3. The simulation model of the hydraulic mechanical composite transmission device is established and simulated. The results show that the designed hydraulic mechanical composite transmission has good speed regulation characteristics and can meet the complicated and varied working conditions of the tractor.